2020
DOI: 10.1002/iub.2404
|View full text |Cite
|
Sign up to set email alerts
|

Soy isoflavone genistein inhibits hsa_circ_0031250/miR‐873‐5p/FOXM1 axis to suppress non‐small‐cell lung cancer progression

Abstract: The foods of plants provide the rich nutrition and have protective function in human diseases, including cancers. Genistein is a major isoflavone constituent in soybeans, which has an anti-cancer role in non-small-cell lung cancer (NSCLC). Nevertheless, the mechanism underlying the anti-cancer function of genistein in NSCLC remains largely unknown. NSCLC cells (H292 and A549) were exposed to genistein. Circular RNA hsa_circ_0031250 (circ_0031250), microRNA (miR)-873-5p and forkhead box M1 (FOXM1) abundances we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…Notably, miR-873-5p has been shown to be a critical suppressor for several cancer types, such as colon cancer, 15 cervical cancer, 16 papillary thyroid cancer, 17 and NSCLC. 18 These results strongly hint that miR-873-5p is involved in MCF2L-AS1-mediated effects on the CSC-like traits of NSCLC cells. Indeed, our results showed that miR-873-5p negatively regulates the CSC-like traits of NSCLC cells.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Notably, miR-873-5p has been shown to be a critical suppressor for several cancer types, such as colon cancer, 15 cervical cancer, 16 papillary thyroid cancer, 17 and NSCLC. 18 These results strongly hint that miR-873-5p is involved in MCF2L-AS1-mediated effects on the CSC-like traits of NSCLC cells. Indeed, our results showed that miR-873-5p negatively regulates the CSC-like traits of NSCLC cells.…”
Section: Discussionmentioning
confidence: 78%
“…RNA‐pull down combined with luciferase reporter analysis confirmed that lncRNA MCF2L‐AS1 indeed can bind to miR‐873‐5p. Notably, miR‐873‐5p has been shown to be a critical suppressor for several cancer types, such as colon cancer, 15 cervical cancer, 16 papillary thyroid cancer, 17 and NSCLC 18 . These results strongly hint that miR‐873‐5p is involved in MCF2L‐AS1‐mediated effects on the CSC‐like traits of NSCLC cells.…”
Section: Discussionmentioning
confidence: 91%
“…It is known that nutrition is very important in lung health and defense [46][47][48]. Protection against lung cancer and the radioprotective effect of soy isoflavones are well described in the bibliography [49,50]. Soy isoflavones seem to increase chemotherapy induced cell death in different types of lung cancer [51,52].…”
Section: Soy and The Respiratory Systemmentioning
confidence: 99%
“…In addition, genistein is a soy-derived isoflavone that can play a beneficial role in cancer treatment ( 130 ). Genistein can inhibit the progression of NSCLC by regulating the circ_0031250/miR-873-5p/FOXM1 axis ( 131 ).…”
Section: The Role Of Mir-873-5p In Cancer Treatmentmentioning
confidence: 99%
“…Knockout of circ_0004507 can up-regulate the expression of miR-873-5p and inhibit the progression of laryngeal cancer ( 137 ). circ_0031250 can promote the proliferation, migration, and invasion of NSCLC cells by inhibiting the miR-873-5p/FOXM1 axis ( 131 ). circZKSCAN1 can inhibit the progression, proliferation, migration, and invasion of HCC by down-regulating the miR-873-5p/DLC1 axis, thereby hindering the occurrence and development of HCC ( 138 ).…”
Section: The Regulation Of Mir-873-5p In Human Cancermentioning
confidence: 99%